PENDAMPINGAN PEMBELAJARAN AL-QUR’AN DAN PEMBEBASAN PEREMPUAN DARI FEMISIDA DI MA’HAD AL-QUR’AN UNIVERSITAS PTIQ JAKARTA - Mulia, Musda; Al Haqqi, Sabila; Romaida, Romaida; Addaruqutni, Imam; Sholichah, Aas Siti; Darmadi , Didik (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This article discusses the role of the Qur'an in liberating women from femicide that occurred in pre-Islamic Arab culture. The study focuses on analyzing Surah An-Nahl (16): 58–59 and Surah At-Takwir (81): 8–9, which describe the practice of burying female infants alive and the negative attitudes of Arab society toward the birth of girls. This research employs a qualitative method using library research, with data sources drawn from classical and contemporary Qur'anic exegesis (tafsir), as well as other relevant literature. Data analysis is conducted using a descriptive-analytical approach. The data is examined by presenting the interpretations of Qur'anic commentators (mufassir) on the selected verses and analyzing their implications for the discourse on women's liberation in Islam. The findings show that the Qur'an explicitly criticizes the practice of burying female infants alive. Killing, discrimination, and unjust treatment of women are actions that contradict Islamic values and must be eradicated from society. The Qur'an seeks to liberate women from injustice and to uphold their dignity. In the contemporary context, new forms of femicide and violence against women continue to occur. Therefore, the values of women's liberation found in the Qur'an must be continually upheld and promoted through education, critical exegesis, legal reform, and social advocacy